PENINGKATAN PRODUKTIVITAS KERJA MELALUI MOTIVASI DAN DISIPLIN KERJA POLITEKNIK LP3I JAKARTA KAMPUS JAKARTA UTARA - Featy Octaviany; Fitri Shabrina (JURNAL LENTERA BISNIS, 2019)
The purpose of this study was to study the motivation and work discipline on the work productivity of the Polytechnic LP3I Jakarta North Jakarta Campus. This research was conducted with a method of collecting data by distributing questionnaires to 30 employees of the LP3I Jakarta Polytechnic North Jakarta Campus. This research uses quantitative descriptive method with multiple linear analysis techniques. The hypothesis test used is the F test and t test.The results of this study indicate the relationship between motivation (X1) to work productivity of 0.594, as well as work discipline variables (X2) to work productivity (Y) has a relationship of 0.389. Motivation (X1) and work discipline (X2) on work productivity (Y) are carried out simultaneously showing a relationship of 0.608 and having an influence of 39.60%.The relationship between motivation and dissipilin work on work productivity both partially and simultaneously has a strong correlation. LP3I Jakarta Polytechnic Motivation and work discipline towards the work motivation of North Jakarta Campus have better work motivation and discipline competence.Keywords: Motivation, Work Discipline and Work Productivity.